The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2298/pan1304473w
|View full text |Cite
|
Sign up to set email alerts
|

Which global stock indices trigger stronger contagion risk in the Vietnamese stock market? Evidence using a bivariate analysis

Abstract: This paper extends recent investigations into risk contagion effects on stock markets to the Vietnamese stock market. Daily data spanning October 9, 2006 to May 3, 2012 are sourced to empirically validate the contagion effects between stock markets in Vietnam, and China, Japan, Singapore, and the US. To facilitate the validation of contagion effects with market-related coefficients, this paper constructs a bivariate EGARCH model of dynamic conditional correlation coefficients. Using the correlation conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Thus, Vietnam is one of the fastest growing economies in Southeast Asia (Nikkei Asian Review, 2019). As an emerging nation with a transitional economy, the country adopted many capitalist business traits since the early 1990s (Wang & Lai, 2013). Many corporate financial decisions -especially capital structure -are based not only on the characteristics of the company but also on the volatility of macroeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Vietnam is one of the fastest growing economies in Southeast Asia (Nikkei Asian Review, 2019). As an emerging nation with a transitional economy, the country adopted many capitalist business traits since the early 1990s (Wang & Lai, 2013). Many corporate financial decisions -especially capital structure -are based not only on the characteristics of the company but also on the volatility of macroeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, a contagion impulse is investigated which is defined as process of shock transmission across the markets. This effect could be the consequence of asymmetric information resulting from changes in asset correlation coefficients, Wang and Lai (). Many authors, inter alia, Longin and Solnik (); Mun (); Chang and Su () found asymmetric volatility in the conditional variances of financial assets.…”
Section: Methodological Approachmentioning
confidence: 99%
“…To understand the expected risk premium in emerging markets we must first point out that emerging markets differ significantly from developed markets. Overall, emerging markets are less developed; have a lower quality of governance; a higher country credit risk; show more mutual synchronous market movement, as reported by Randall Merck, Bernard Yeung, and Wayne Yu (2000), Nikola Gradojević and Eldin Dobardžić (2013); are exposed to contagion risk, as argued by Kuan-Min Wang and Hung-Cheng Lai (2013); are facing illiquidity, shown by Boško Živković and Jelena Minović (2010); and have a smaller influence of individual stock characteristics. They also have higher market concentration with small samples of firms accounting for large proportions of aggregate market values, in the structure of financial intermediation dominating the banking sector, unlike the US where financial markets have dominance in the financial architecture.…”
Section: Ex-ante Equity Premium As a Price Of Equity Risk: An Importamentioning
confidence: 96%